Etnomatematika dalam Proses Pembuatan Pom-Pom Sagu: Kajian Budaya dan Matematika di Desa Tabarfane, Kabupaten Kepulauan Aru: Etnomatematika Dalam Proses Pembuatan Pom-Pom Sagu: Kajian Budaya Dan Matematika Di Desa Tabarfane, Kabupaten Kepulauan Aru - Temarwut Djamiri, Amalia; Lessy, Djaffar; Sopamena, Patma; Rahman, Abdillah (Journal of Mathematics Learning Innovation, 2026)
This study aims to describe and analyze the mathematical concepts embedded in the traditional production of sago pom-pom in Tabarfane Village, Aru Islands Regency. Using a qualitative approach with an interpretive ethnographic design, data were gathered through direct observation, in-depth interviews with pom-pom producers, and field documentation. Findings reveal that each stage of production—washing, drying, sifting, burning, cooling, cutting, sun-drying, and packaging—naturally embodies mathematical activities as categorized by Bishop: counting, measuring, locating, designing, explaining, and playing. These activities involve geometric concepts such as cylinders, circles, and triangular prisms, alongside basic arithmetic operations and equivalent fractions, all practiced intuitively within a framework of local wisdom. These findings affirm that ethnomathematics present in sago pom-pom production not only contributes to cultural preservation but also holds strategic value as a contextual learning resource in mathematics education